Aspek Hak Asasi Manusia dalam Pembentukan Peraturan Perundang-Undangan di Indonesia - Rifai, Ahmad; Khanif, Al; Mulya, Kukuh Budi (Universitas Jember, 2023)
The title of this article is the Human Rights Aspects In The Establishment Of Law Regulations In Indonesia. The background of this writing is whereas in the constitution, one of the elements of a rule of law is the fulfillment of human rights in it, so that in this case the red thread can be drawn in this research there are still problems in the implementation of norms for the formation of laws and regulations in Indonesia. This study uses a normative juridical, the problem approach used is a statute approach and a conceptual approach. Based on the result of this research, first, that the urgency of human rights values is the basis for forming laws and regulations in Indonesia because human rights values are natural and its position has been mandated in the 1945 Constitution. Second, that laws and regulations are still found both at the central and regional levels those who have not implemented human rights aspects. Third, that the drafting of this legislation was carried out by the Directorate of Human Rights Instruments as an effort to fill the legal vacuum for a public need for human rights, the Directorate of Human Rights Instrument.Keywords: Human Rights, State Law, Legislation.